2017
DOI: 10.1371/journal.pone.0177506
|View full text |Cite
|
Sign up to set email alerts
|

Maternal prenatal anxiety and child COMT genotype predict working memory and symptoms of ADHD

Abstract: Maternal prenatal anxiety is an important risk factor for altered child neurodevelopment but there is uncertainty concerning the biological mechanisms involved and sources of individual differences in children’s responses. We sought to determine the role of functional genetic variation in COMT, which encodes catechol-O-methyltransferase, in the association between maternal prenatal anxiety and child symptoms of ADHD and working memory. We used the prospectively-designed ALSPAC cohort (n = 6,969) for our primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 51 publications
(61 reference statements)
2
36
0
Order By: Relevance
“…Davis et al ( N  = 91) found no evidence of a sex-dependent association between maternal prenatal plasma cortisol concentrations and child (ages 6–9) cognitive functioning [33]. Finally, data from two independent cohorts ( N = 6969 and N  = 425) provided no evidence of sex dependence in an association between prenatal maternal anxiety and offspring working memory [23]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Davis et al ( N  = 91) found no evidence of a sex-dependent association between maternal prenatal plasma cortisol concentrations and child (ages 6–9) cognitive functioning [33]. Finally, data from two independent cohorts ( N = 6969 and N  = 425) provided no evidence of sex dependence in an association between prenatal maternal anxiety and offspring working memory [23]. …”
Section: Resultsmentioning
confidence: 99%
“…Zhu et al ( N  = 1765) found a sex-specific association: Severe PNLEs were associated with increased odds of clinical ADHD symptoms in preschool boys but not girls [54]. In the ALSPAC data ( N  = 6969), there was a significant interaction of maternal anxiety and a COMT genetic variation in predicting child ADHD symptoms at age 4, but no evidence of sex dependence [23]. Finally, in the Rhea Study ( N  = 288), maternal psychopathology symptoms were associated with child ADHD symptoms, but there was no evidence of sex dependence [27].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the prevalence of maternal antenatal antidepressant use in our sample corresponded to the general Finnish population (Malm et al., ), supporting the representativeness of our sample. On the other hand, while we focused on the effects of maternal depressive symptoms on child neurodevelopment, depression is highly comorbid with anxiety also in the perinatal period (Falah‐Hassani, Shiri, & Dennis, ), and maternal antenatal anxiety has also been shown to affect child neurodevelopment (Buss, Davis, Hobel, & Sandman, ; O'Donnell et al., ; Van den Bergh et al., ). Hence, further studies disentangling the unique effects of maternal depression and anxiety on child neurodevelopment are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations in the coding of the enzyme catechol-Omethyltransferase (COMT), have been showed to influence the association between maternal prenatal anxiety, child ADHD symptoms and infant's working memory. COMT is involved in the breakdown of catecholamine neurotransmitters including dopamine, noradrenaline and adrenaline (O'Donnell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%